2017
DOI: 10.1002/yd.20268
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Efficacy and Leadership Competency Development

Abstract: This chapter covers the role of students' self-efficacy in developing their leadership competencies. Practical strategies and recommendations are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Akanbi (2013) found similar results for racial minorities and concluded that African American college students tended to be inspired to pursue careers as entrepreneurs when they held positive beliefs about their ability to be leaders. Conversely, when college students had low efficacy about their leadership abilities, they tended to avoid adversity and not pursue leadership opportunities (Machida‐Kosuga, 2017). Self‐efficacy beliefs have also been positively linked to college students' achievement and continued education toward a particular field in several studies (Gregor et al, 2020; Roy et al, 2018).…”
Section: Self‐efficacy Beliefs Influence College Students' Career Aspirationsmentioning
confidence: 99%
“…Akanbi (2013) found similar results for racial minorities and concluded that African American college students tended to be inspired to pursue careers as entrepreneurs when they held positive beliefs about their ability to be leaders. Conversely, when college students had low efficacy about their leadership abilities, they tended to avoid adversity and not pursue leadership opportunities (Machida‐Kosuga, 2017). Self‐efficacy beliefs have also been positively linked to college students' achievement and continued education toward a particular field in several studies (Gregor et al, 2020; Roy et al, 2018).…”
Section: Self‐efficacy Beliefs Influence College Students' Career Aspirationsmentioning
confidence: 99%
“…The Efficacy domain of employee development reflects employees’ belief in their ability to develop a specific capacity essential for high‐level performance. Self‐efficacy related to learning can be defined as “beliefs regarding one's capability for learning new skills and utilizing the learned skills in performance situations” (Machida‐Kosuga, , p. 23).…”
Section: Six‐domain Model Of Training and Developmentmentioning
confidence: 99%
“…Machida‐Kosuga () asserts that the desired level of learning self‐efficacy for those in a preparatory or training context should be high. Individuals must be able to be adaptable, resilient, and persistent in their learning; if they are discouraged or cannot overcome roadblocks, they may opt out of the learning experience altogether (Machida‐Kosuga, ). Blanchard and Thacker () stress that it is critical to enhance self‐efficacy beliefs around the content area of the training, especially for those whose self‐efficacy is low, before learning can take place.…”
Section: Six‐domain Model Of Training and Developmentmentioning
confidence: 99%